2005
DOI: 10.1111/j.0014-3820.2005.tb00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Beneficial Mutations in Escherichia Coli

Abstract: Micromutational models of adaptation have placed considerable weight on antagonistic pleiotropy as a mechanism that prevents mutations of large effect from achieving fixation. However, there are few empirical studies of the distribution of pleiotropic effects, and no studies that have examined this distribution for a large number of adaptive mutations. Here we examine the form and extent of pleiotropy associated with beneficial mutations in Escherichia coli. To do so, we used a collection of independently evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
95
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 29 publications
12
95
4
Order By: Relevance
“…In an effort to distinguish these explanations, one study specifically focused on pleiotropic effects of beneficial mutations in five different environments. Mutations that were beneficial in the selected environment tended to be beneficial in others, and although there were exceptions, limited antagonistic pleiotropy was observed [45], [46]. Here, we also report limited antagonistic pleiotropy with five beneficial mutations with an increased sample size of 1,920 environments from our initial Biolog screen (Table S1).…”
Section: Discussionmentioning
confidence: 50%
“…In an effort to distinguish these explanations, one study specifically focused on pleiotropic effects of beneficial mutations in five different environments. Mutations that were beneficial in the selected environment tended to be beneficial in others, and although there were exceptions, limited antagonistic pleiotropy was observed [45], [46]. Here, we also report limited antagonistic pleiotropy with five beneficial mutations with an increased sample size of 1,920 environments from our initial Biolog screen (Table S1).…”
Section: Discussionmentioning
confidence: 50%
“…With the exception of lethal selection or niche creation [11] experiments, most other studies have demonstrated that the fitness advantage conferred by a mutation is maintained across environments and conditions [9,10]. In other words, they have found that beneficial mutations are generally not severely compromised in other environments [10].…”
Section: Discussionmentioning
confidence: 99%
“…Early artificial selection experiments showed that improving one trait often worsens another, suggesting that AP is not uncommon (Mather and Harrison, 1949; Rice, 1992; Cooper and Lenski, 2000; Ostrowski et al, 2005). Consistently, a Drosophila study proposed over 1000 candidate genes that are subject to sexual antagonism, based on correlations between gene expression levels and organismal fitness across 15 genotypes and two sexes (Innocenti and Morrow, 2010).…”
Section: Introductionmentioning
confidence: 99%